VIABILITY OF LACTIC ACID BACTERIA ON GLUTINOUS CORN FLOUR (zea mays Ceratina) WITH MICROWAVE-COOLING MODIFICATION - Isra, Muh; Mutsyahidan, Arif Murtaqi Akhmad; Saman, Widya Rahmawaty (Universitas Negeri Gorontalo, 2024)
This study aims to evaluate the viability of lactic acid bacteria (LAB) on glutinous corn flour (Zea mays ceratina) modified through a microwave-cooling process. Glutinous corn flour was selected due to its nutritional content that supports LAB growth, while the microwave-cooling modification was applied to improve the quality and sterility of the medium. The LAB used in this study was Lactobacillus plantarum IIA-1A5, which has probiotic potential with broad applications in the food industry. This research used an experimental design with two bacterial treatments to determine LAB viability. The parameters observed included LAB viability and prebiotic activity. The results showed that the optimal microwave-cooling treatment produced a LAB viability of 1.40 Log CFU/mL and a prebiotic activity of 0.31 Log CFU/mL after 24 hours of incubation. Therefore, glutinous corn flour modified with microwave-cooling demonstrates significant potential as an effective and practical medium for LAB growth in fermented food products. This study contributes to the development of sustainable local food technology based on natural raw materials.